Guide to Spanish Idioms - Raymond H. Peirson (USA Passport Books, 1989)
Guide to Spanish Idioms is packed with more than 2,500 idioms, English equivalents, and explanation of typical use. It also includes common obstacles such as nouns that change meaning according to gender or number. Users will find idioms that relate to moods, appearance, personal relations, unpleasant situations and difficulties, and more!
Keywords: Nonfiction; Language; Dictionary; Reference